2018
DOI: 10.14740/jocmr3285w
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Treatment Consideration in Diabetic Patients

Abstract: Although orthodontic treatment is commonly indicated for young healthy individuals, recent trends showed an increase in number of older individuals undergoing orthodontic interventions. The increased age resulted in a proportionate increase in the prevalence of systemic diseases facing dentists during orthodontic procedures, especially diabetes mellitus. This necessitates that dentists should be aware of the diagnosis of diabetes mellitus and its early signs particularly in teeth and oral cavity. It is also es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
(33 reference statements)
0
15
0
2
Order By: Relevance
“…Although our initial intention was to search for and document any clinical trial or prospective/ retrospective epidemiologic study with the involvement of patients or patient records of orthodontically treated individuals under the metabolic condition of diabetes, this was ultimately not applicable. There is a gap in the existing literature between human and animal research characterized by complete lack of evidence emerging from clinical research (Almadih et al, 2018;Burden et al, 2001), as no study could be identified except for isolated case reports (Maia, Monini, Jacob, & Gandini, 2011;Reichert, Deschner, & Jäger, 2009) while animal research has been identified as the sole source of evidence (Holtgrave, & Donath, 1989;Najeeb et al, 2017).…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…Although our initial intention was to search for and document any clinical trial or prospective/ retrospective epidemiologic study with the involvement of patients or patient records of orthodontically treated individuals under the metabolic condition of diabetes, this was ultimately not applicable. There is a gap in the existing literature between human and animal research characterized by complete lack of evidence emerging from clinical research (Almadih et al, 2018;Burden et al, 2001), as no study could be identified except for isolated case reports (Maia, Monini, Jacob, & Gandini, 2011;Reichert, Deschner, & Jäger, 2009) while animal research has been identified as the sole source of evidence (Holtgrave, & Donath, 1989;Najeeb et al, 2017).…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…No attention is given to ARIAs in orthodontia and orthognathic surgery. To date, there is no gold standard for the treatment of postoperative infections in orthodontic surgery and the use of prophylactic antibiotics before some orthodontic procedures (orthodontic band placement, separator placement, or screw insertion) in patients with a medical history that reveals the presence of diseases affecting the host defense system (aging, patient on corticosteroids or bisphosphonates or anticoagulants, diabetes mellitus, HIV/AIDS) since they are at high risk of developing oral infection [37,169]. Endocarditic prophylaxis is indicated only during the initial placement of orthodontic bands (not brackets).…”
Section: Focus On Orthodontia-associated Surgerymentioning
confidence: 99%
“…Oral complications of DM are multiple and include xerostomia, burning mouth and/or tongue, candida infection, altered taste, progressive periodontal disease, dental caries, acetone breath, oral neuropathies, parotid enlargement, sialosis and delayed wound healing. These complications can occur even when the blood glucose is well-controlled due to impaired neutrophil function, but they are all more severe in poorly controlled DM (Al-Maskari et al, 2011; Almadih et al, 2018; Leite et al, 2013; Patel et al, 2009). Well-controlled DM is not a contraindication for orthodontic treatment (Patel et al, 2009); however, orthodontic treatment should be avoided in patients with poorly controlled DM as they are more likely to suffer from periodontal involvement (Almadih et al, 2018).…”
Section: Endocrinologymentioning
confidence: 99%
“…These complications can occur even when the blood glucose is well-controlled due to impaired neutrophil function, but they are all more severe in poorly controlled DM (Al-Maskari et al, 2011; Almadih et al, 2018; Leite et al, 2013; Patel et al, 2009). Well-controlled DM is not a contraindication for orthodontic treatment (Patel et al, 2009); however, orthodontic treatment should be avoided in patients with poorly controlled DM as they are more likely to suffer from periodontal involvement (Almadih et al, 2018). If in doubt, the orthodontist should liaise with the patient and their diabetic team in the provision of care.…”
Section: Endocrinologymentioning
confidence: 99%